2006
DOI: 10.1002/ajim.20350
|View full text |Cite
|
Sign up to set email alerts
|

Worker participation in change processes in a Danish industrial setting

Abstract: Implementation of a comprehensive intervention was followed by improved employee perceptions of the company's safety standards and the psychosocial work environment, as well as by substantial reductions in the incidence of eczema and occupational accidents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 26 publications
(25 reference statements)
0
42
0
2
Order By: Relevance
“…Although occupational health has a long and varied tradition of worker participation [Wallerstein and Weinger, 1992;Rasmussan et al, 2006], the involvement of workers as genuine research partners tends to be more recent [Israel et al, 1989]. Yet as several earlier studies [Israel et al, 1989;Arcury et al, 1999Arcury et al, , 2001Lee and Krause, 2002;Lee et al, 2008] have suggested, CBPR with low-wage, largely immigrant, or minority workers may improve the quality of our research by complementing academic concerns with rigor and reliability with community concerns about the local relevance and coherence in all stages of the research, including the development of the research question, the appropriateness of sampling, recruitment and instrument design, and the interpretation, dissemination and use of findings.…”
Section: Resultsmentioning
confidence: 99%
“…Although occupational health has a long and varied tradition of worker participation [Wallerstein and Weinger, 1992;Rasmussan et al, 2006], the involvement of workers as genuine research partners tends to be more recent [Israel et al, 1989]. Yet as several earlier studies [Israel et al, 1989;Arcury et al, 1999Arcury et al, , 2001Lee and Krause, 2002;Lee et al, 2008] have suggested, CBPR with low-wage, largely immigrant, or minority workers may improve the quality of our research by complementing academic concerns with rigor and reliability with community concerns about the local relevance and coherence in all stages of the research, including the development of the research question, the appropriateness of sampling, recruitment and instrument design, and the interpretation, dissemination and use of findings.…”
Section: Resultsmentioning
confidence: 99%
“…The findings paper for this project (published elsewhere) demonstrates contextualisation of interventions is pivotal to achieving workplace culture change and improvements in health knowledge and behaviour in the participating truck drivers. This is an effect seen in other health promotion interventions in blue-collar workplaces [42,43,[50][51][52][53]. Future projects should seek to engage participants to a greater extent in the design of a social media health promotion intervention.…”
Section: Principal Resultsmentioning
confidence: 99%
“…In that sense, the process of action research can be generalized to other companies interested in this process. We believe that this approach has shown its strength to improve the psychosocial factors at work (see previous empirical studies of -Participatory -ActionResearch, such as Heaney, et al, 1993;Huxham & Vangen, 2003;LeBlanc, Hox, Schaufeli, Taris & Peeters, 2007;Pasmore & Friedlander, 1982;Rasmussen, et al, 2006;Whyte, 1989;see Dollard, LeBlanc & Cotton, 2008, for a review). So we should take its use into account when designing a WSI.…”
Section: Limitations and Future Researchmentioning
confidence: 95%